IMPLEMENTASI BIMBINGAN TEMAN SEBAYA BERBASIS NILAI-NILAI ISLAM DALAM MENCEGAH PERILAKU BULLYING DI MADRASAH IBTIDAIYAH: KAJIAN TAFSIR QS. AL-HUJURAT AYAT 11–12 DAN HADIS TENTANG LARANGAN MENYAKITI SESAMA MUSLIM - Nadila Farahita; Rifanto Bin Ridwan; Emmi Kholilah Harahap (STKIP Subang, 2026)
Bullying is one of the social problems that can hinder students' development and create Bullying is a social problem that can hinder students’ development and create an unfavorable learning environment in Madrasah Ibtidaiyah. This study aims to analyze the implementation of Islamic value-based peer counseling in preventing bullying using a literature review method with a qualitative approach through content analysis of various relevant sources. The results show that peer counseling is effective as a preventive strategy because it enhances empathy, communication, and social support among students. The integration of Islamic values, particularly QS. Al-Hujurat verses 11–12 and the Hadith of the Prophet Muhammad (SAW), strengthens students’ character development in terms of mutual respect, mindful speech, and avoidance of degrading others. Thus, Islamic value-based peer counseling can create a safe, harmonious, and bullying-free madrasah environment.